The microbial contamination in the surgery operation theater at Al-zahraa General Teaching Hospital - Akmam Ali Habeeb (Al-Qadisiyah Journal of Pure Science, 2018)
One of the most disturbing problems in the hospitals and especially surgery operation theaters (OT) is the microbial contamination which is a challenging issue and difficult to fight. For such reason, we had initiated this study to investigate the presence of this contamination in the OT in Al-zahraâ€™a General Teaching hospital, Al-Kut, Iraq.  Five hunderds swabs were performed from the (OT) cultivated in different culture media to study macroscopic and microscopic features, the biochemical tests were done for primary identification of bacteria.. The study was done during March, July, and August of 2016, the rates of the isolated bacteria from the OT were 15.13%, 11.91%, and 15% respectively with a significant presence (pË‚0.05) in March. While the rates of the total Gram negative bacteria isolated from the OT were 49.65%, 54.27%, and 78.27% respectively with a significant occurrence (pË‚0.05) in September. These rates for the Gram positive bacteria isolated from the OT were 48.5%, 20.57%, and 23.20% respectively. The isolated fungi and yeast were at rates of 4.02%, 2.19%, and 3.10% respectively with significant presence of the Candida albicans during March. E. coli was significantly was the highest among the isolated coliform bacteria (pË‚0.05); 35.45%, 37.48%, and 42.85% respectively. The current study confirms the presence of high contamination of the surgery operation room by bacteria and fungi.